2013
DOI: 10.6061/clinics/2013(11)13
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction and cardiovascular diseases: a systematic review of prevalence

Abstract: The aim of this study was to conduct a systematic review of the literature regarding the prevalence of sexual dysfunction in patients with cardiovascular diseases. An article search of the ISI Web of Science and PubMed databases using the search terms "sexual dysfunction”, “cardiovascular diseases”, “coronary artery disease", “myocardial infarct" and “prevalence” was performed.In total, 893 references were found. Non-English-language and repeated references were excluded. After an abstract analysis, 91 referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
1
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 48 publications
4
47
1
13
Order By: Relevance
“…Reduced sexual activity and satisfaction, erection problems, and orgasmic problems have been described in these patients (36). The patients in the present study also reported similar difficulties (data not shown).…”
Section: Discussionsupporting
confidence: 74%
“…Reduced sexual activity and satisfaction, erection problems, and orgasmic problems have been described in these patients (36). The patients in the present study also reported similar difficulties (data not shown).…”
Section: Discussionsupporting
confidence: 74%
“…This is a situation that increases likelihood that bias. Significant relation between erectile dysfunction and presence of these diseases has already shown in previous studies [2][3][4][5][6].…”
Section: Dear Editormentioning
confidence: 73%
“…For instance, many patients with atrial fibrillation use antihypertensive or antiarrhythmic drugs. And in various studies, it has shown that these drugs might cause erectile dysfunction [2][3][4][5][6][7]. It might be useful if the authors could provide further information on this issue.…”
Section: Dear Editormentioning
confidence: 97%
“…Using the SS is beneficial both for objective risk stratification in patients and for providing optimal revascularization strategy by enhancing collaboration between a surgeon and a cardiologist [9]. It has been reported that ED is present in 46% of males with CAD and that there is a correlation between severity of CAD and ED [3]. The aim of the present study was to investigate the relationship between ED severity and SS in patients with CAD who underwent coronary angiography.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, CVD comprises many risk factors for sexual dysfunction. In individuals with CVD, pathological processes influencing vascular configurations also influence the arteries that provide blood supply to the genital organs and lead to high rates of sexual dysfunction both in males and females [3]. In the European Association of Urology (EAU) guidelines, ED is defined as "the persistent inability to attain and maintain an erection sufficient to permit satisfactory sexual performance" [4].…”
Section: Introductionmentioning
confidence: 99%